Image of Geopolitical and Cultural Catastrophe in the Poetry of Oleg Chukhontsev - Shchepacheva, Inna Vladimirovna; Skvortsov, Artem Eduardovich; Galimullina, Alfia Foatovna; Zinin, Sergey Alexandrovich (International Journal of Criminology and Sociology, 2022)
Oleg Chukhontsev is one of the most outstanding modern Russian poets. In his creativity, there was only one period when he almost did not create from late 1980 to the second half of the 1990s. This is the time of post-Soviet disintegration, and for the majority of the Russian population, it was a difficult experience. In the rare works created by Chukhontsev at that time, the country’s geopolitical and cultural catastrophe is somehow interpreted. As it usually happens with a poet, it naturally combines various semantic plans like external realistic and several symbolic. At Southern Night, Chukhontsev has embodied the feeling of a complete end and this work perfectly combines deeply personal motives and motives that convey the image of a geopolitical and cultural catastrophe. As the author states, everything has died, both his former poetics (personal meaning) and his former country (general meaning). The poet has lost the gift of speech because he ceased to feel an organic connection with his native land since it was “seriously ill and was almost at death”. By the time of the creation of Closing the Season Chukhontsev, as a poet, had managed to renew himself.